Evaluation of Hepatic, Renal and Cerebral Function Test in Preeclampsia-Eclampsia Syndrome and its Correlation to Maternal and Fetal Outcome - Patra, Sangita; Das, Suchibrata; Dalai, Sujata; Mistri, Pallab Kumar (Birat Journal of Health Sciences, 2022)
Introduction: Hypertensive disorders complicates 5-10% of pregnancies all over the world and its incidence in India was found to be 10.08% as per data of National Eclampsia Registry (NEP).Objectives: The objectives of this study were to determine the incidence of abnormal liver, renal and cerebral function test among patients with preeclampsia and eclampsia and their correlation to maternal and fetal outcome.Methodology: The study was a prospective cohort study comparing the maternal and fetal outcomes of preeclampsia and eclampsia patients with abnormal parameters (cases; n=50) and pre-eclampsia and eclampsia patients with normal parameters (controls; n=50).  Both case and control were examined clinically apart from biophysical and biochemical investigation.Results:  Deranged LFT was present in approximately 56% -70% of cases. Serum albumin was decreased in 80% of cases. Prothrombin time (PT) was raised in 48% of cases. Abnormal GFR, urea, creatinine and uric acid level were present in 44%, 10%, 10% and 64% of cases. Among all the pregnancy outcomes in preeclampsia and eclampsia cases with abnormal LFT, preterm labour, PPH, IUFD, meconium stained liquor and neonatal death had significant “p” value